PP.24.20: PRELIMINARY DATA OF NONINVASIVE HEMODYNAMIC STUDY IN PREGNANT PATIENTS FOLLOWED ON AN ESH HYPERTENSION EXCELLENCE CENTER. (June 2015) - Abad-Cardiel, M.; Garcia-Donaire, J.; Barbero-Pedraz, A.; Rodilla, E.; Sierra, C.; Domenech, M.; Martell-Claros, N.
Abstract : Objective: Integrated hemodynamic management using a non-invasive hemodynamic study based on thoracic electrical bioimpedance, HOTMAN devices, allows clinicians to evaluate the status of tissue perfusion. Data on hypertensive patients show a predominant alteration in volemia (hypervolemia) as the more frequent change in hemodynamic modulation (Identification of the hemodynamic modulators and hemodynamic status in uncontrolled hypertensive patients. Viigimaa M). To define the hemodynamic situation of pregnant hypertensives in order to study this population hemodynamic characteristics. Design and method: This is a transversal study of pregnant hypertensive patients attended at our hypertension unit. We reviewed epidemiologic data, hemodynamic patterns, pharmacological treatment if needed and data from the fetal development. Results: Data from 15 pregnancy women were included. Mean age was 36, 4 years old (Range 41 to 29). Three of them had personal history of preeclampsia. Brachial BP previous to hemodynamic study was 119, 6/71, 3 mmHg (range systolic BP 103–150 mmHg, diastolic BP 56–113 mmHg). Mean heart rate was 85 bpm (range 71–101 bpm). 41, 5 % of the studies was done throughout the third trimester, 41, 5% during the second and only 17% in the first. Vasoconstriction, found in 45% of the whole group, was found in the 85% of the treated group. None alteration of volemia was found in any of the women studied. Tissue perfusion, estimated by cardiac index, corrected by gestational week was reduced in 93.3%, 100% of treated. Left ventricular output, estimated by stroke index was low in 93, 3% of the studies. None of the women had a growth fetal restriction; only in 14% had a pathological eco Doppler of uterine arteries. Conclusions: Pregnant hypertensive patients have vasoconstriction as the more frequent hemodynamic alteration. In pregnant hypertensive patients, non-invasive hemodynamic study may be useful in the follow up, but longitudinal studies are needed.